PERMA-Profiler for adolescents: validity evidence based on internal structure and related constructs - Fernandes, Iorhana; Zanini, Daniela Sacramento; Peixoto, Evandro Morais (Frontiers in Psychology, 2024)
The PERMA model of well-being has gained prominence in the study of well-being by the Positive Psychology movement. However, the model has been little studied regarding its applicability in different populations, such as adolescents. This study sought to evaluate the psychometric properties of the PERMA-Profiler instrument for Brazilian adolescents, as well as the measurement invariance for different age groups and gender, and investigate the relation with external variables. Confirmatory Factor Analysis and Multigroup Confirmatory Factor Analysis were used to test the internal structure and invariance of the PERMA-Profiler. Reliability was determined with McDonald's Omega and composite reliability. A total of 1197 adolescents between 11 and 19 years old from different regions of Brazil participated. The results of the confirmatory factor analysis indicated that the five correlated factors model was the most appropriate, presenting good factor loadings and adequate reliability. The scale proved to be invariant for adolescents of different age groups and gender. Correlations with associated variables were significant and moderate to strong, showing positive relations between positive emotions and well-being, and negative relations with negative affects and depressive and anxiety symptoms. These results contribute to the understanding of well-being in adolescence and highlight the importance of promoting different components of well-being for adolescents' mental health.